2016
DOI: 10.1155/2016/6567473
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery plus Hyperthermic Intraperitoneal Chemotherapy for Management of Peritoneal Sarcomatosis: A Preliminary Single-Center Experience from Saudi Arabia

Abstract: Aim. To report our preliminary single-center experience with cytoreductive surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) for management of peritoneal sarcomatosis (PS). Methods. Eleven patients were retrospectively analyzed for perioperative details. Results. Cytoreduction completeness (CC-0/1) was achieved in all patients with median peritoneal cancer index (PCI) of 14 ± 8.9 (range: 3–29). Combination cisplatin + doxorubicin HIPEC chemotherapy was used in 6 patients. Five patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Currently, the only approach that provided an improved survival for PS is CRS/HIPEC when CC0 is achieved (6,16,17). In the past decade, multiple institutional experiences were reported (16)(17)(18)(19)(20)(21)(22) about the impact of CRS/HIPEC on survival in PS and agreed on OS of 24−28 months and DFS of 14−18 months. We have reported that a complete cytoreduction and low PCI score appear to be important factors in the outcome of patient with PS (6).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only approach that provided an improved survival for PS is CRS/HIPEC when CC0 is achieved (6,16,17). In the past decade, multiple institutional experiences were reported (16)(17)(18)(19)(20)(21)(22) about the impact of CRS/HIPEC on survival in PS and agreed on OS of 24−28 months and DFS of 14−18 months. We have reported that a complete cytoreduction and low PCI score appear to be important factors in the outcome of patient with PS (6).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been 4 retrospective single-institution series and 1 phase I study examining the role of cytoreductive surgery (CRS) and intra-peritoneal chemotherapy in the treatment of peritoneal sarcomatosis [[42], [43], [44], [45], [46]]. However, mixed outcomes have been reported and there is marked heterogeneity in histological types, and inclusion and exclusion criteria across the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine sarcoma is a rare and aggressive disease, representing 3–9% of uterine cancers . This malignancy has poor prognosis due to its biological behavior, high rates of recurrence, and ineffective treatment with the current therapeutic modalities . Progression to PS frequently occurs after initial treatment ; however, PS may be present at the first presentation of US .…”
Section: Discussionmentioning
confidence: 99%
“…It results from the intra‐abdominal spread of malignant disease involving the peritoneal surface. PS is characterized by an increased risk of recurrence and poor long‐term survival (median overall survival 6–15 months), indicating lack of an effective treatment . Classic therapeutic modalities such as radiotherapy, chemotherapy, and palliative surgery have not been shown to improve patient outcomes .…”
Section: Introductionmentioning
confidence: 99%